Optimization and the Influence of Additive on the Interfacial Bonding between Cocoa Fruit Shell Powder and Polypropylene-Based Composite - A, Ago M.; J, Gani; Y, Joshau; M, Bifam; M, Dass P.; J, Martha (Darul Yasin Al Sys, 2024)
Agricultural residues are excellent alternative materials to lignocellulosic materials because they are inexpensive, easily processed, plentiful, and renewable. Optimization and the influence of additive on the interfacial bonding between Cocoa fruit shell powder and Polypropylene-based composite was carried out. The methods use include, water absorption, tensile strength, impact strength, hardness, and SEM. From the studies it was shown that the water absorption property of the composites decreases with increase in CaCO3 content in the matrix for all the composites investigated. The tensile strength of the modified composite increases with additive. The impact strength results are 4.17 kJ/m3 to 5.58 kJ/m3 for unused/treated composites, 3.47 kJ/m3 to 5.27 kJ/m3 for waste/treated composites. It was observed that the hardness for the modified composite ranges from 39 MPa to 63 MPa for unused polypropylene/treated and, 33.43 MPa to 52.77 MPa for waste polypropylene/treated composites. Based on SEM images, it can be said that the use of Alkaline treated Cocoa fruit shell powder and microcrystalline cellulose resulted in better-dispersed structures in the polymer matrix. This project mitigates environmental impact without compromising structural integrity by exploring Theobroma cacao and Polyethylene modified composite materials.